Mechanism and Prevention of Acute Knee Joint Injury During Exercise - Hou, Junjie; Li, Ruixuan; Wang, Haoming; Wang, Zihao (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Anatomically, the knee joint is the most complex joint in the human body. It consists of the medial and lateral condyles of the femur, the medial and lateral condyles of the tibia, and the patella. From the perspective of kinematics, the knee joint is one of the most critical joints to complete various actions in the human movement. Due to these two characteristics, it has also become a high incidence of sports injuries. Especially in sports activities, sports knee injury is extremely common, so it must be paid attention to, especially professional athletes, denying that it may affect the careers. This study mainly analyzes the common sports injuries of the knee joint and their mechanisms, and discusses the common sports injuries of the knee joint, as well as the mechanism of the knee joint injury and how to prevent the knee joint injury from three aspects, so as to prevent the small problems and help the development of sports.